Protein Quality Control in Neurodegenerative Diseases - Morimoto, Richard I.; Christen, Yves.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The health of the proteome depends upon protein quality control to regulate the proper synthesis, folding., translocation, and clearance of proteins. The cell is challenged constantyl by environmental and physiological stress, aging, and the chronic expressions of disease associated misfolded proteins. Substantial evidence supports the hypothesis that the expression of damaged proteins initiates a cascade of molecular events that leads to Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis, Huntington's disease, and other diseases of protein conformation.
The Regulation and Function of the Heat Shock Response by Eric Guisbert and Richard I. Morimoto -- The Endoplasmic Reticulum Unfolded Protein Response and Neurodegeneration by David Ron -- Proteostasis and the aging pathways by Ian Nicastro and Andrew Dillin -- The Membrane Sources of Macroautophagy by Daniel J. Klionsky, Melinda A. Lynch-Day, Jiefei Geng, and Wei-Lien Yen -- Selective Autophagy in Cellular Quality Control by Susmita Kaushik and Ana Maria Cuervo -- Quality Control of Proteins and Organelles by Autophagy by Noboru Mizushima -- The Role of the Co-Chaperone BAG3 in Selective Macroautophagy: Implications for Aging and Disease by Christian Behl -- Predicting Fates in Models of Neurodegenerative Disease: Longitudinal Measures of Protein Homeostasis in Live Neurons by Steven Finkbeiner -- Therapeutic Potential of Longevity Modulators as Neuroprotective Targets in Neurodegenerative Disease by Rafael Vazquez-Manrique, Cendrine Tourette and Christian Neri -- Subject code.
Keywords: Medicine; Neurosciences; Neurochemistry; Biomedicine; Neurosciences; Neurochemistry; Molecular Medicine